Berättelser om det förbjudna: Begär mellan kvinnor i svensk litteratur 1900-1935 - Borgström, Eva (Kriterium, 2016)
"Same-sex love was forbidden by law until 1944, and in culture it continued to be taboo, but it has always existed there. The prohibition created tensions which art and literature could play with. Narratives about forbidden love show this through well-known authors such as Agnes von Krusenstjerna, Maria Sandel, Karin Boye and Frida Stéenhoff, and less well-known ones like Gertrud Almqvist, Margareta Suber, Lydia Wahlström and the pseudonym Elsa Gille. The book investigates literary narratives about women's love for women and the ideas about the forbidden contained in them. What strategies did the authors use to get round the ban on the mention of the topic? Are there any utopian visions of how everything could be arranged in a different and better way? And how does the literature relate to other theories about same-sex love? Berättelser om det förbjudna: Begär mellan kvinnor i svensk litteratur 1900-1935 ("Stories of the Forbidden: Desire between Women in Swedish Literature 1900-1935") is a free-standing continuation of Kärlekshistoria: Begär mellan kvinnor i 1800-talets litteratur ("Love Story: Desire between Women in Nineteenth-century Literature", 2008). Together the books span over 100 years of Swedish literary history, making them the most comprehensive study available in the field in Sweden and Scandinavia. Eva Borgström is associate professor of comparative literature and lecturer at the Department of Literature, History of Ideas, and Religion at the University of Gothenburg. She has formerly worked at the National Secretariat for Gender Research and the Department of Gender Studies.